1994
DOI: 10.1073/pnas.91.9.3569
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of osteoclast bone-resorption activity by inhibition of nitric oxide synthase.

Abstract: We have examined the effects of modulating nitric oxide (NO) levels on osteoclast-mediated bone resorption in vitro and the effects of nitric oxide synthase (NOS) inhibitors on bone mineral density in vivo. Diaphorase-based histochemical staining for NOS activity of bone sections or highly enriched osteoclast cultures suggested that osteoclasts exhibit substantial NOS activity that may account for basal NO production. Chicken osteoclasts were cultured for 36 hr on bovine bone slices in the presence or absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
178
3
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(198 citation statements)
references
References 15 publications
14
178
3
3
Order By: Relevance
“…Furthermore, chronic administration of certain NOS inhibitors in adult rats significantly diminishes bone formation, independent of any marked affect on blood pressure. 12,29 Although such studies have tended to suggest that this was attributable more to inhibition of iNOS 12,29 than eNOS the compounds used are not sufficiently selective in their action to be able to state unequivocally which isoform(s) are involved. 37 Previous studies on NOS gene knockout mice have indicated that in certain tissues other NOS isoforms can substitute for the function of the disrupted one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, chronic administration of certain NOS inhibitors in adult rats significantly diminishes bone formation, independent of any marked affect on blood pressure. 12,29 Although such studies have tended to suggest that this was attributable more to inhibition of iNOS 12,29 than eNOS the compounds used are not sufficiently selective in their action to be able to state unequivocally which isoform(s) are involved. 37 Previous studies on NOS gene knockout mice have indicated that in certain tissues other NOS isoforms can substitute for the function of the disrupted one.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Numerous studies have also shown that administration of NOS inhibitors to rats in vivo leads to a reversible osteopenia. 12,28,29 Rat models of ovariectomyinduced osteopenia have also revealed that osteoporotic bone loss can be alleviated by administration of NO donors and conversely, inhibition of endogenous NO suppresses the bone-conserving action of estradiol. 18 These observations have demonstrated that the synthesis and activity of both eNOS and iNOS is significant in bone biology although there is consensus that under physiological conditions eNOS probably represents the major NOS activity regulating bone formation.…”
mentioning
confidence: 99%
“…52 NO synthases have been demonstrated in both osteoclasts and osteoblasts. 53,54 NO may be the mediator by which oestrogen or androgen therapy improves BMD. Nitrate use is associated higher BMD 32 and prevents bone loss in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in accord with a previous study in transgenic mice overexpressing eNOS that exhibit altered hemodynamics and resistance to LPS when compared with WT animals (32) and suggest that eNOS-derived NO may be important in vivo in expediting host defense. In addition, enhancement of NF-B activity and pro-inflammatory protein expression by NO may underlie control of osteoclast function, which appears to be regulated by a combination of constitutive and inducible NOS activity in vitro and in vivo (33,34).…”
Section: Discussionmentioning
confidence: 99%